Building maximal green sequences via component preserving mutations - Bucher, Eric (Ars mathematica contemporanea, 2020)
We introduce a new method for producing both maximal green and reddening sequences of quivers. The method, called component preserving mutations, generalizes the notion of direct sums of quivers and can be used as a tool to both recover known reddening sequences as well as find reddening sequences that were previously unknown. We use the method to produce and recover maximal green sequences for many bipartite recurrent quivers that show up in the study of periodicity of ?$T$?-systems and ?$Y$?-systems. Additionally, we show how our method relates to the dominance phenomenon recently considered by Reading. Given a maximal green sequence produced by our method, this relation to dominance gives a maximal green sequence for infinitely many other quivers. Other applications of this new methodology are explored including computing of quantum dilogarithm identities and determining minimal length maximal green sequences.
Keywords: cluster algebra; direct sum; direktna vsota; klasterska algebra; maksimalno zeleno zaporedje; maximal green sequence